(3CSGSjGJ Yde GdGbJUGO (B:s (3eONd dOQGSI CUhd GdEbJUGO GdSjGSj habG ddeHGOF GdSGFOI ddfXe GdEbJUGOjI GdebGQfI (B/s - (3MTjT, YGOd CMeOs; (3ShRj YOdj, fGTOs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2001)
(3GdJYQja HGdEbJUGO GdSjGSj cYde GLJeGYj aj VhA GdeTcdI GdEbJUGOjI ceMOO YGe dfWGbg GdehVhYj(B- (3GdeYQa hGdbhGfjf GdEbJUGOjI GddBReI ddJYQa Ydi GdfTGW GdEbJUGOj HGdeLJeY hGdGUhd GdeJWd(Bd(3I dVeGf GSJeQGQ hJLOO OhQI GdCfJGL hGdJhRjY aj fWGbg Ydi fMh QTjO(B- (3GdeTcdI GdEbJUGOjI hcjajI Md GdeLJeYGJ GdQCSeGdjI hGdETJQGcjI dgG habG ddCUhd GdeJYGQa YdjgG aj GbJUGOjGJ GdfXGejf GdQCSeGdj hGdETJQGcj Yf GdShb hGdJNWjW(B.s
Keywords: (3Yde GdEbJUGOs